Laboratory method of simulation of hydroabrazive wear of materials - Шевеля, В. В.; Дворук, В. И.; Посташ, А. С.; Радченко, А. В. (Proceedings of National Aviation University (archive), 2000)
Proposed is the technique of reduction of test time by combination in one experiment of twc types of samples interaction in hydroabrazive medium